2001
DOI: 10.1017/s0714980800012277
|View full text |Cite
|
Sign up to set email alerts
|

Senior Centres: Who Participates?

Abstract: RÉSUMÉCet article porte sur la participation des aîné(e)s aux centres du troisième âge, la fréquence de fréquentation, les changements en matière de participation sur une période de quatre ans et sur les facteurs connexes. Les données proviennent d'une étude longitudinale menée à Winnipeg et dans huit petits centres du Manitoba auprès de 1 399 personnes âgées de 65 ans et plus interviewées en 1991/92 et 956 interviewées de nouveau en 1995. Environ une personne sur cinq avait fréquenté un centre du troisième âg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 23 publications
1
29
1
Order By: Relevance
“…A Norwegian study conducted by Boen et al (2010) showed that age was the most significant variable predicting senior center attendance; the older a person, the greater their use. However, some researchers (Krout, 1983;Strain, 2001) found no relationship between age and usage. A curvilinear relationship has also been found (Krout et al, 1990;Turner, 2004).…”
Section: Sociodemographic Factorsmentioning
confidence: 99%
See 4 more Smart Citations
“…A Norwegian study conducted by Boen et al (2010) showed that age was the most significant variable predicting senior center attendance; the older a person, the greater their use. However, some researchers (Krout, 1983;Strain, 2001) found no relationship between age and usage. A curvilinear relationship has also been found (Krout et al, 1990;Turner, 2004).…”
Section: Sociodemographic Factorsmentioning
confidence: 99%
“…In general, the predictor variables frequently used in analyses of senior center attendance can be grouped into four major categories: sociodemographic factors, health, social interaction, and accessibility (Krout et al, 1990;Miner et al, 1993;Strain, 2001). The findings of previous studies are summarized as follows.…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations